Oocyte Donation and Endometriosis: What Are the Lessons? - Hauzman, Erik E.; Garcia-Velasco, Juan A.; Pellicer, Antonio (Seminars in Reproductive Medicine, 2013)
Outcomes of in vitro fertilization cycles in women with endometriosis are significantly worse than in patients without this condition. The impact of endometriosis on ovarian reserve and the quality of retrieved oocytes seems evident. Lower implantation rates, however, raise the question whether this finding is purely the consequence of lower number and poorer quality of embryos, or whether it also reflects compromised endometrial receptivity. Oocyte donation provides an interesting model to investigate reproductive outcome because factors affecting the oocytes are excluded, especially if cycles using oocytes derived from the same donor are analyzed. These studies have shown lower implantation rates in nonendometriotic patients who received oocytes from women with endometriosis, whereas healthy donated oocytes have proven to contribute to a pregnancy with similar chances in women without the disease. The question still to be answered is whether this situation applies for natural cycles or whether it is the use of gonadotropin-releasing hormone analogs and hormonal replacement therapy used for endometrial priming in oocyte recipients that reestablishes an adequate uterine environment. Using a genomic tool based on microarray technology (endometrial receptivity array), the study of differential gene expression in the eutopic endometrium of endometriosis patients undergoing oocyte donation treatment is still underway.
Keywords: endometriosis; oocyte donation; endometrial receptivity